Sociodemographic parameters of Esophageal Cancer in northwest India: A regional cancer center experience of 10 years - Akhil Kapoor; Vanita Kumar; Mukesh Kumar Singhal; Raj Kumar Nirban; Surender Kumar Beniwal; Harvindra Singh Kumar (Wolters Kluwer Medknow Publications, 2015)
Background: Despite various advances in the treatment of Esophageal Cancer (EC), being one of the least responsive tumors to cancer therapy, the overall prognosis remains poor. Therefore, it is significant to understand various sociodemographic factors associated with EC to find out various schemes for primary prevention of the disease. Materials and Methods: This is a retrospective analysis of medical records of the EC patients registered in the regional cancer center of northwest India from January 2003 to December 2012. The site of the disease and the histology were also recorded in addition to the various sociodemographic parameters. Results: Out of 55,742 patients registered in our hospital; 3,667 were diagnosed to have EC. Male:female ratio was 1.15:1. The mean age was 54.6 ± 11.74 years; 66.15% of the patients were illiterate and 48.6% belonged to the low socioeconomic status. Smoking and alcohol consumption were identified as risk factors in 48 and 25.6% of the patients, respectively. Conclusions: The etiology in majority of the patients is linked to tobacco and alcohol, thus, modification of life style with limiting the use of addictions may be an effective strategy in the prevention of this dreaded and mostly incurable disease.